Pengaruh Influencer Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Scarlett Dengan Media Sosial Sebagai Variabel Intervening - Yolanda JN; Emil Salim; Della Asmaria Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of influencers and product quality on purchasing decisions for Scarlett products, with social media serving as an intervening variable. The study employs a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 for analysis. The population and sample consist of Management students from UPI YPTK Padang. The results indicate a positive and significant influence of influencers on social media and of product quality on social media. There is a positive but insignificant influence of influencers on purchasing decisions and of product quality on purchasing decisions. However, there is a positive and significant influence of social media on purchasing decisions. Social media acts as a mediator between influencers and purchasing decisions, as well as between product quality and purchasing decisions.